Software Engineering and Formal Methods. SEFM 2022 Collocated Workshops AI4EA, F-IDE, CoSim-CPS, CIFMA, Berlin, Germany, September 26-30, 2022, Revised Selected Papers - Masci, Paolo; Bernardeschi, Cinzia; Graziani, Pierluigi; Koddenbrock, Mario; Palmieri, Maurizio (Cham : Springer International Publishing : Imprint: Springer, 2023)
This volume constitutes the revised selected papers from the four workshops collocated with the 20th International Conference on Software Engineering and Formal Methods, SEFM 2022, held in Berlin, Germany, in September 2022. The 19 full papers presented together with 9 short papers in this volume were carefully reviewed and selected from a total of 39 submissions. The contributions that are collected in this volume have been selected from the presentations at the following workshops: AI4EA 2022: First Berlin Workshop on Artificial Intelligence for Engineering Applications; F-IDE 2022: 7th Workshop on Formal Integrated Development Environment; CoSim-CPS 2022: 6th Workshop on Formal Co-Simulation of Cyber-Physical Systems; CIFMA 2022: 4th International Workshop on Cognition: Interdisciplinary Foundations, Models and Applications.
Artificial Intelligence -- Co-Simulation -- Formal Methods -- Formal Modelling -- Verification and Validation -- High Confidence Systems -- Integrated Development Environment -- Interdisciplinary Foundations of Cognition -- Logics; Simulation; Software Engineering; System Engineering.
Keywords: Software engineering; Computer systems; Computer science; Computer programming; Software Engineering; Computer System Implementation; Theory of Computation; Programming Techniques